From Hyponatremia to Osmotic Demyelination: A Clinical Odyssey and Lessons Learned - Abdul Razack, Jafrin Sadiq; Asgar Ali, Sahil; Hussaini, Syeda Juveria; Khaled Aldoseri, Saud; Rajagopal, Harshavardhan; Calvin Ossanam, Antony; Akram, Ibtisam; Khalili, Viorica (International Journal of Innovative Research in Medical Science, 2024)
A 76-year-old female presented with acute confusion and delirium of 3 days duration. The patient was admitted to the ICU in a state of acute confusion. History taken from the patient’s daughter revealed that the patient had nausea, vomiting, diarrhea, and fever two days before admission. Blood tests and imaging were ordered, and after reviewing the results, a diagnosis of osmotic demyelination syndrome (ODS) was made.